Is more financial literacy always beneficial? An investigation through a mediator - Biwei Chen; Christos Giannikos; Jun Lou (Journal of Risk and Financial Management, 2023)
We study the impact of financial literacy on financial risk preference. When financial literacy is measured jointly by actual and self-assessed scores, we find compelling evidence of a valley-shaped relationship between actual financial literacy and risk preference. At a given level of self-assessment, as actual financial literacy increases, the willingness to take risks initially decreases and then rises. Actual financial literacy is modeled to impact risk preference through self-assessed financial literacy, the mediator; this mediation effect is significant. Furthermore, increasing actual financial literacy has a positive (negative) effect in underconfident (overconfident) individuals on several financial behaviors.
Keywords: D14; G53; 650; financial literacy; mediation effect; perception bias; risk preference